Design to Encourage Reframing and Transformations through Digital Story telling and Analogical Thinking - Lee, Chien Sing *; Ooi, Ean-Huat (The World Academy of Research in Science and Engineering, 2020)
With increasingly saturated markets and technological convergences globally, product differentiation is getting more challenging. We hypothesize that design, design-thinking, computational thinking and digital coding-storytelling aimed at encouraging reframing, and transforming would encourage anlogical thinking and among the 21st century skills, ultimately, fractal thinking. Fractal thinking enables identification of patterns, which can be repeated but varied and decomposable to different levels of abstraction. In a study on expert systems analysts and programmers, curation and sharing of story-based media and analogical coding are encouraged. Next, analogical derivatives and their characteristics are mapped to PwC’s worlds. These enable identification of design factors (tangible and intangible scaffolds) for the development of a code-storytelling-analogical-fractal thinking system. The significance is extension from design thinking and computational thinking to analogical and ultimately, fractal thinking; the derivation of types of analogies and their characteristics, corresponding to PwC’s worlds. Future work situates learning within the Restorative Innovation-obscure-feature hypothesis framework.